Mesoporous Silica vs. Organosilica Composites to Desulfurize Diesel - Ribeiro, Susana O.; Granadeiro, Carlos M.; Corvo, Marta C.; Pires, João; Campos-Martin, José M.; de Castro, Baltazar; Balula, Salete S. (Frontiers in Chemistry, 2019)
The monolacunary Keggin-type [PW11O39]7- (PW11) heteropolyanion was immobilized onto the porous framework of mesoporous silicas, namely SBA-15 and an ethylene-bridged periodic mesoporous organosilica (PMOE). The supports were previously functionalized with a cationic functional group (N-trimethoxysilypropyl-N,N,N-trimethylammonium, TMA) for the successful anchoring of the anionic polyoxometalate. The PW11@TMA-SBA-15 and PW11@TMA-PMOE composites were evaluated as heterogeneous catalysts in the oxidative desulfurization of a model diesel. The PW11@TMA-SBA-15 catalyst has shown a remarkable desulfurization performance by reaching ultra-low sulfur levels (<10ppm) after only 60 min using either a biphasic extractive and catalytic oxidative desulfurization (ECODS) (1:1 MeCN/diesel) or a solvent-free catalytic oxidative desulfurization (CODS) system. Furthermore, the mesoporous silica composite was able to be recycled for 6 consecutive cycles without any apparent loss of activity. The promising results have led to the application of the catalyst in the desulfurization of an untreated real diesel supplied by CEPSA (1335 ppm S) using the biphasic system. The system has proved to be a highly efficient process by reaching desulfurization values higher than 90% for real diesel during 3 consecutive cycles.